Recombinant Respiratory Syncytial Virus (RSV) Bearing a Set of Mutations from Cold-Passaged RSV Is Attenuated in Chimpanzees - Whitehead, Stephen S. (American Society for Microbiology, 1998)
A set of five missense mutations previously identified by nucleotide sequence analysis of subgroup A cold-passaged (cp) respiratory syncytial virus (RSV) has been introduced into a recombinant wild-type strain of RSV. This recombinant virus, designated rA2cp, appears to replicate less efficiently in the upper and lower respiratory tracts of seronegative chimpanzees than either biologically derived or recombinant wild-type RSV. Infection with rA2cp also resulted in significantly less rhinorrhea and cough than infection with wild-type RSV. These findings confirm the role of the cp mutations in attenuation of RSV and identify their usefulness for inclusion in future live attenuated recombinant RSV vaccine candidates.